54.0k views
0 votes
HELPPL Enter the solution from least to greatest (x-2)(3x+3)=0

User Arshdeep
by
4.7k points

2 Answers

3 votes

Answer:

x = -1 x = 2

Explanation:

(x-2)(3x+3)=0

Using the zero product property

x-2 =0 3x+3 =0

x=2 3x = -3

x = -3/3

x = -1

User Andreas Walter
by
4.8k points
4 votes

Answer:

x = -1, 2

Explanation:

Step 1: Write out equation

(x - 2)(3x + 3) = 0

Step 2: Solve each individual root

x - 2 = 0

x = 2

3x + 3 = 0

3x = -3

x = -1

Step 3: Arrange from least to greatest

-1 < 2

So x = -1, 2

User AHS
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.